Three-dimensional TiO2/Au nanoparticles for plasmon enhanced photocatalysis. (9th February 2018) - Yu, Jianyu; Zhou, Lin; Wang, Yang; Tan, Yingling; Wang, Zhenlin; Zhu, Shining; Zhu, Jia
Abstract: The mechanisms of plasmonic nanostructures assisted photocatalytic processes are fundamental and of great importance and interest for decades. Therefore, we adopt a unique porous structure of three-dimensional TiO2 /Au nanoparticles to experimentally explore the potential mechanisms of rhodamine B (RhB) based photocatalytic degradation. The highly efficient absorbance measured across the entire ultraviolet and infrared regions shows the broadband light harvesting capability and photocatalytic activity, in which the direct bandgap transition, plasmon sensitization as well as the plasmonic photothermal effect can be beneficial for the photocatalytic reaction. The RhB photocatalytic degradation experiments were conducted systematically under solar irradiance with finely chosen optical filters. Apart from the ultraviolet-driven degradation of TiO2, the plasmon assisted photocatalytic rate of our TiO2 /Au structure can be enhanced by >30% as compared to the referenced TiO2 structure (equivalent to 2–4 times promotion with respect to the same quantity of the active material TiO2 ). Detailed wavelength-dependent analyses have revealed that the visible-driven degradation rate can be enhanced by 10 times because of the plasmon sensitization effect; while infrared-driven degradation rate is enhanced by 4 times as well for the plasmonic photothermal effect, respectively. Our experimental results may provide a clear understanding for the wavelength-dependent plasmon enhanced photocatalytic processes.